Antibacterial Activity of Different Extract of Albizia Lebbeck Stem Bark - Chhimwal, Jyoti; Sharma, Anu; Saini, Priyanka; Kabra, Mahaveer; Bhandari, Sanjay (Asian Journal of Pharmaceutical Research and Development, 2013)
Albizia lebbeck (family Fabaceae), is used as a medicinal plant and also finds its application in pharmaceutical industry which is attributed to a credible biologically active component present in stem bark. A study was conducted to explore antibacterial activity of Albizia lebbeck different extract of stem bark (hexane, methane, aqueous) on two bacterial species S.aureus and E. coli.It was found out that S. aureus was highly susceptible to aqueous and methanolic extract of A. lebbeck whereas no activity was observed with hexane extract. In other hand E. coli was resistant to all above extracts.